Electro-optic and dielectric properties of new binary ferroelectric and antiferroelectric liquid crystalline mixtures. Issue 9 (15th July 2017) - Fitas, Jakub; Marzec, Monika; Kurp, Katarzyna; Żurowska, Magdalena; Tykarska, Marzena; Bubnov, Alexej
ABSTRACT: Several new binary liquid crystalline mixtures have been designed and their properties were studied by complementary methods. It has been shown that even both pure components used for the mixture design possess the ferroelectric behaviour; the induced antiferroelectric smectic phase has been detected for one of the prepared mixtures. The phase diagram has been constructed and the existence of the antiferroelectric phase was confirmed by switching time and dielectric spectroscopy measurements. Some of the resulted mixtures possess very high values of the tilt angle that reaches close below 45° degrees at saturation. Values of spontaneous polarisation were found within 50–200 nC/cm 2 in dependence of the mixture's composition. Due to specific properties, the obtained mixtures might be interesting for further design of multicomponent mixtures and formulation of the advanced nanocomposite systems. Graphical Abstract: